A narrative analysis of a teacher educator's professional learning journey. Issue 3 (26th May 2016) - Vanassche, Eline; Kelchtermans, Geert
Abstract: This article reports on a narrative analysis of one teacher educator's learning journey in a two-year professional development project. Professional development is conceived of as the complex learning processes resulting from the meaningful interactions between the individual teacher educator and his/her working context. Our analysis indicates that the capacity to manage such interactions contributes strongly to teacher educators' experience of vulnerability. We analytically describe three strategies (building positive self-esteem, sustaining moral commitment and purpose, and strategical compliance) to cope with this vulnerability and their impact on processes of professional development as well as the outcomes of it. Understanding the role of the working context – and vulnerability as a structural characteristic of that context – in professional development processes adds to existing knowledge of teacher educators' professional lives and development.